Academic Expatriates Adjustment to Foreign Assignments - Dewan, Sabira (2010)
As globalisation has led to increasing international mobility, the contemporary expatriate management literature has focused on managers and corporate executives. The higher education literature focuses on the internationalisation of education systems, particularly growth in international strategic alliances between universities. By comparison, the academic expatriate even though not a new phenomenon remain an under-research group. Specifically, at a time when internationalisation is a major trend in higher educational institute very little is known about academic expatriate. Moreover, much of the expatriate literature adopts a positivist non-theoretical approach using quantitative methodologies and large-scale studies that leave the perspective of the individual relatively unexplored. This study seeks to address that gap. The study uses a qualitative research methodology based on narratives collected through in-depth interviews and is located within an interpretive paradigm. Expatriation is at the centre of this study. Drawing on data from interviews with three British academics expatriate living in Malaysia, it explores their adjustment process. Along with that, decision to expatriate and their experience of expatriation is also explored. The study reports that adventure is a dominant theme behind the decision to expatriate which substantiates Richardson & Mckenna (2002) the notion of expatriate as ‘explorer’. The academic expatriate like business expatriate faced adjustment problem and most of the problems can be linked to culture difference. The academic expatriate tried to fit in by changing themselves but at the same time tried to incorporate their culture in the work place. In terms of social life they felt they did not have to change. Training on cross-cultural issue was not provided to the academic expatriate and most felt that training could influence their adjustment process in a positive way. Even though all three participants were living in Malaysia and they had come for the same country each had very different experience of expatriation.